Life cycle of thrips (Megalurothrips spp.) on long bean (Vigna unguiculata) / Mohamad Amir Shah Yusop ... [et al.] - Yusop, Mohamad Amir Shah; Mohammed, Anisah; Abdul Aziz, Noorshilawati; Abdullah, Nur Suraya (2011)
The study has been done to identify the life cycle of Megalurothrips spp. starts from egg, larvae, pre pupa, pupa and adult stages. The host plants that have been used in the study were long bean (Vigna unguiculata). The objective is to determine the life cycle of thrips from egg until the emergence of adult. Result from the experiment found that the life cycle of thrips range from 15 to 19 days with mean of life cycle was 16.25 ± 0.11 days. As conclusion, the result obtained could be useful information as a guideline data to formulate Integrated Pest Management (lPM) in term of controlling techniques such as in selecting type of insecticide, mode of action and also combination of others techniques such as biological control in controlling thrips